Teachers’ Experiences of the Curriculum Transition from the 2013 Curriculum to the Merdeka Curriculum in Elementary Learning at SD Agia Sophia Medan - Ria Duma Situmeang; Enzelina Tambunan; Evi Sitorus; Medianti Simanjuntak (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
Curriculum transition is an important educational process because it influences teachers’ instructional planning, classroom practices, assessment strategies, learning media, and students’ learning experiences. In Indonesia, the transition from the 2013 Curriculum to the Merdeka Curriculum requires teachers to adapt to more flexible, student-centered, project-based, and competency-oriented learning. This study aims to describe teachers’ experiences in implementing learning during the transition from the 2013 Curriculum to the Merdeka Curriculum at SD Agia Sophia Medan. This study employed a descriptive qualitative design. Data were collected through direct classroom observation and semi-structured interviews with five elementary school teachers. The data were analyzed thematically through data reduction, data display, interpretation, and conclusion drawing. The findings show that teachers experienced both opportunities and challenges during the curriculum transition. The opportunities included greater student creativity, more active participation, project-based learning experiences, and stronger student independence. However, teachers also faced several challenges, including the need to prepare new teaching media, limited learning resources, limited infrastructure, students’ low learning independence, unequal student understanding, and the need to adapt from familiar 2013 Curriculum routines. The study also found that four of the five teachers preferred the Merdeka Curriculum, while one teacher preferred the 2013 Curriculum because of familiarity and the availability of teaching materials. This study concludes that the success of curriculum transition depends strongly on teacher readiness, school support, learning media availability, professional adaptation, and continuous mentoring.